The Effectiveness of Constitutional Supervision Judges by the Constitutional Court Honorary Council : (Study of the Constitutional Court Honorary Council Decision Number 2/MKMK/L/11/2023) - Fernanda, Diah Ayu; Jabbar, Achmad Arbi' Nur Badrotin; Rachmaddany, Saifullah Yudha Noorman; Maghfiroh, Ajeng Ayu (Reformasi Hukum, 2024)
After the Judicial Commission is no longer an institution that carries out the function of supervising the behavior of constitutional judges, and the existence of the Constitutional Court Ethics Council in 2020 was abolished. The supervisory institution of the Constitutional Court is currently only held by the MKMK, which is only on an ad hoc or temporary basis. This research will examine the effectiveness of the MKMK's role in supervising constitutional judges. The method used in this research is normative juridical. The results of this research provide an illustration that constitutional judges need to have a supervisory institution, this of course starts from the freedom that judges have so that it is not misused. This research succeeded in showing that the MKMK decision Number 2/MKMK/L/11/2023, which states that the Chief Justice of the Constitutional Court is proven to have committed a serious violation of the provisions of ethics and behaviour of constitutional judges, then given the sanction of removal as chairman of the Constitutional Court, without being accompanied by dismissal as a constitutional judge, raises issues regarding the absence of legal certainty and clarity of the supervisory institution of the behaviour of constitutional judges as well as the effectiveness of MKMK in carrying out its supervisory duties.